Measurement of Medial Head Gastrocnemius Muscle Contraction Strength in Basic Sepak Takraw Techniques Using Electromyogram Signals - Rusli, Rusli ully; Ruslan, Ruslan; G., Sarifin; Arimbi, Arimbi; Qibtiyah, Mariyal (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to measure the strength of contraction of the gastrocnemius medial head muscle in basic techniques sepak sila using electromyogram signals. The subjects in this research were 3 South Sulawesi sepak takraw athletes. EMG signal measurement using the Trigno™ Wireless EMG System. The output data is the results of the EMG signal, the Root Mean Square value of each muscle component measured. The data analysis technique uses quantitative descriptive. The results of EMG signal measurements produce RMS values for each muscle measured as follows: (1). The subject produced the largest first EMG signal from the right gastrocnemius medial head muscle, 0.44631mV with an RMS value of 93.009mV, and the largest left gastrocnemius medial head muscle, 0.33889mV with an RMS value of 61.302mV. (2). The subject produced the second largest right gastrocnemius medial head muscle EMG signal of 1.66238mV with an RMS value of 38.7856mV, and the largest left gastrocnemius medial head muscle of 1.37871mV with an RMS value of 25.6827mV. (3). The subject produced the third largest right gastrocnemius medial head muscle EMG signal of 2.02191mV with an RMS value of 76.7969mV, and the largest left gastrocnemius medial head muscle of 0.37397mV with an RMS value of 47.3252mV. It was concluded that the third subject produced the highest muscle EMG strength which occurred in the right gastrocnemius medial head muscle signal and the smallest EMG signal in the left gastrocnemius medial head.